Diversity of Mangrove Plants in Karimunjawa National Park - Subiyati; Amin Retnoningsih; Enni Suwarsi Rahayu (Postgraduate, University of Mataram, 2024)
Karimunjawa National Park (TNK) area is ± 111,625 hectares covering 27 islands located in Jepara Regency, Central Java at the northern tip of Java Island. Karimunjawa became Karimunjawa National Park (TNK) based on the Decree of the Minister of Forestry and Plantation No.78/Kpts-II/1999 because it has high diversity. The complexity of ecosystems in TNK is interesting to study, such as coral reef ecosystems, mangrove forests, lowland tropical rainforests, seagrass meadows, seaweed, and coastal forests. The mangrove forest in Karimunjawa National Park is a unique ecosystem because it consists of many mangrove species. However, data on the diversity of mangrove species on this island has not been widely described. This study aims to reveal mangrove diversity in Karimunjawa National Park as a rescue strategy and explore the potential of mangrove biodiversity. This research is a descriptive study using the cruising method to explore mangrove species diversity. The location of mangrove diversity exploration is mangrove forest in Karimunjawa National Park. The results found 14 families consisting of 38 mangrove species. Among the 38 species, 24 species are true mangroves, while the other 14 species are associated with mangroves.